Cross-protection mediated by a βC1 deletion DNAβ associated with Tomato yellow leaf curl China virus - YE Jian; QING Ling; ZHOU Xue-ping (浙江大学学报. 农业与生命科学版)
Pre-inoculation of a βC1 deletion DNAβ (Y10ΔC1β) associated with Tomato yellow leaf curl China virus (TYLCCNV) Y10 isolate (Y10) with cognate virus could mediate cross-protection to challenge-infection of cognate or heterogenous DNAβ. Both Nicotiana benthamiana and N. glutinosa plants pre-inoculated with Y10+Y10ΔC1β exhibited mild symptoms after challenge inoculation with Y10 +Y10β, but protection effects in N. benthamiana were better than in N. glutinosa, and protection effects against cognate DNAβ were better than DNAβ associated with Tobacco curly shoot virus (TbCSV).